Hadith #3284 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Ayoub bin Musa bin 'Amr bin Sa'id أيوب بن موسى بن عمرو; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) prayed in a Khamisah* that had markings on it. Then he said: ‘These markings distracted me. Take it to Abu Jahm and bring me an Anbijaniyyah.’”**
Grade:

Hadith #3285 - Sunan Ibn Majah - Abu al-Malih; Bakr bin Khlf al-Basri بكر بن خلف البصري; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Yazid bin Zari' يزيد بن زريع (Sunan Ibn Majah)
“I entered upon ‘Aishah and she brought out to me a thick waist wrap of the type made in Yemen, and one of these cloaks that are called Mulabbadah,* and she swore to me that the Messenger of Allah (ﷺ) had passed away in them.”
Grade:

Hadith #3286 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
It was narrated from ‘Ubadah bin Samit that the Messenger of Allah (ﷺ) prayed in a Shamlah tied with a knot.
Grade:

Hadith #3287 - Sunan Ibn Majah - Aslam Client Of 'Umar أسلم مولى عمر; ibn Umar; Sufyan bin 'Uyaynah سفيان بن عيينة; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“I was with the Messenger of Allah (ﷺ) and over him was a Najrani upper wrap with a thick border.”
Grade:

Hadith #3288 - Sunan Ibn Majah - Abdul Wahab bin 'Abdul Majeed al-Thaqaf عبد الوهاب بن عبد المجيد الثقفي; Abu Qalaba, 'Abdullah bin Zayd al-Jarmi عبد الله بن زيد بن عمرو; Ahmed bin al-Miqdam أحمد بن المقدام; Khalid bin Mahran al-Hadha' خالد بن مهران الحذاء; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Shadad bin Aus bin Thabit (Sunan Ibn Majah)
“I never saw the Messenger of Allah (ﷺ) insulting anyone, and no garment was ever folded up for him.”*
Grade:

Hadith #3289 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Sa'id al-Khudri; Musa bin Muhammad bin Ibrahim موسى بن محمد بن إبراهيم بن الحارث; Uqba bin Khalid bin 'Uqba - al-Majdar عقبة بن خالد بن عقبة السكوني المجدر (Sunan Ibn Majah)
* “What type of woven sheet?” He said: “A Shamlah.” She said: “O Messenger of Allah, I have woven this with my own hands for you to wear.” The Messenger of Allah (ﷺ) took it, since he needed it. He came out to us wearing it as a lower wrap. So-and-so the son of so-and-so.” – a man whose name he told that day – said: “O Messenger of Allah, how beautiful this sheet is! Let me wear it.” He said: “Yes.” When he went inside he folded it up and sent it to him. The people sa
Grade:

Hadith #3290 - Sunan Ibn Majah - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Mrwan bin Muhammad bin Hsan مروان بن محمد بن حسان الأسدي; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) wore wool and sandals, and he wore coarse, rough garments.”
Grade:

Hadith #3291 - Sunan Ibn Majah - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abu al-Aswad al-Du'ali أبو الأسود الديلي/الدؤلي; ibn Umar; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Ibn Majah)
“Umar bin Khattab put on a new garment and said: Al-hamdu lillahil-ladhi kasani ma uwari bihi ‘awrati, wa atajammalu bihi fi hayati (Praise is to Allah Who has clothed me in something with which I conceal my nakedness and adorn myself in my life). Then he said: ‘I heard the Messenger of Allah (ﷺ) say: “Whoever puts on a new garment and says: Al-hamdu lillahil- ladhi kasani ma uwari bihi ‘awrati, wa atajammalu bihi fi hayati (Praise be to Allah Who has clothed me in something with whi
Grade:

Hadith #3292 - Sunan Ibn Majah - Ikrama عكرمة; Isra'il bin Yonus bin Abi Ishaq إسرائيل بن يونس بن أبي إسحاق; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Is this garment of yours washed or a new one?” He said: “Rather it has been washed.” He said: “Ilbas jadida, wa `ish hamida, wa mut shahida (May you wear new clothes, live a good life and die as martyr).”
Grade:

Hadith #3293 - Sunan Ibn Majah - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Hisham bin 'Urwa هشام بن عروة; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
It was narrated from Abu Sa’eed Al-Khudri that the Prophet (ﷺ) forbade two kinds of dress. Those two types of dress are Ishtimalus- Samma’* and Ihtiba’ in a single garment, with no part of it upon his private part.**
Grade:

Hadith #3294 - Sunan Ibn Majah - Abu al-Ahwus, Salam bin Sulaym al-Hanafi أبو الأحوص سلام بن سليم الحنفي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Muhammad bin Syfy bin Sahl (Sunan Ibn Majah)
Ishtimalus-Samma’ and Ihtiba’, exposing one’s private part to the sky.
Grade:

Hadith #3295 - Sunan Ibn Majah - Bakr bin Khlf al-Basri بكر بن خلف البصري; Muhammad bin Ja'far Ghandar محمد بن جعفر غندر صاحب الكرابيس; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Zayd ibn Thabit (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade two kinds of dress: Ishtimalus-Samma’ and Ihtiba’ in one garment, when you are exposing your private part to the sky.”
Grade:

Hadith #3296 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Adi ibn Hatim al-Tayyi'; Mry bin Qtry al-Kwfy مري بن قطري; Muhammad bin Bashar Bindar محمد بن بشار بندار; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري (Sunan Ibn Majah)
“O my son, if only you could have seen us when we were with the Messenger of Allah (ﷺ), when rain fell on us; you would have thought that we smelled like sheep.”
Grade:

Hadith #3297 - Sunan Ibn Majah - Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Rafi' bin Khadij bin Rafi'; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Ubaya bin Rafa' bin Rafi' عباية بن رفاعة بن رافع; Umar bin 'Ubaid bin Abi Umayya عمر بن عبيد بن أبي أمية الطنافسي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) came out to us one day, wearing a Roman cloak of wool with narrow sleeves. He led us in prayer wearing that, and nothing else.”
Grade:

Hadith #3298 - Sunan Ibn Majah - Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Ata'a bin Yazid al-Laithi al-Junda'i عطاء بن يزيد الليثي الجندعي; Hilal bin Maymun al-Jhny هلال بن ميمون الجهني; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري (Sunan Ibn Majah)
It was narrated from Salman Farisi that the Messenger of Allah (ﷺ) performed ablution, then he turned his woolen cloak that he was wearing inside out and wiped his face with it.
Grade:

Hadith #3299 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hazim, Salma bin Dinar سلمة بن دينار أبو حازم الأعرج; Abu Hurairah; Khlf bin Khlyfh خلف بن خليفة; Marwan bin Mua'wiya al-Fazari مروان بن معاوية الفزاري; Yazid bin Kysan al-Yshkry يزيد بن كيسان اليشكري أبو إسماعيل (Sunan Ibn Majah)
“I saw the Messenger of Allah (ﷺ) marking sheep on their ears, and I saw him wearing a cloak around his wrist.”
Grade:

Hadith #3300 - Sunan Ibn Majah - Abdur Rahman bin Muhammad al-Maharbi عبد الرحمن بن محمد بن زياد المحاربي; Abu Hurairah; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Yahya bin 'Ubaid al-Bahrani يحيى بن عبيد البهراني (Sunan Ibn Majah)
“The best of your garments are the white ones, so wear them and shroud your dead in them.”
Grade:

Hadith #3301 - Sunan Ibn Majah - Abdah bin Sulaiman al-Klabi عبدة بن سليمان الكلابي أبو محمد الكوفي; Hanad bin al-Sari bin Mus'ab هناد بن السري بن مصعب; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“Wear white garments, for they are purer and better.”
Grade:

Hadith #3302 - Sunan Ibn Majah - Muhammad bin 'Abdullah bin Numayr محمد بن عبد الله بن نمير; Rafi' bin Khadij bin Rafi'; Sa'id bin Masrooq Ath-Thawri سعيد بن مسروق الثوري; Ubaya bin Rafa' bin Rafi' عباية بن رفاعة بن رافع (Sunan Ibn Majah)
“The best of that in which you visit Allah in your graves and your mosque is white (garments).”*
Grade:

Hadith #3303 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hammad bin Salama حماد بن سلمة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Whoever lets his garment drag out of pride, Allah will not look at him on the Day of Resurrection.”
Grade:

Hadith #3304 - Sunan Ibn Majah - Abdullah bin Sa'id bin Abi Hind عبد الله بن سعيد بن أبي هند; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Sa'id al-Khudri; Musa bin Muhammad bin Ibrahim موسى بن محمد بن إبراهيم بن الحارث; Uqba bin Khalid bin 'Uqba - al-Majdar عقبة بن خالد بن عقبة السكوني المجدر (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Whoever lets his lower wrap drag out of pride, Allah will not look at him on the Day of Resurrection.” He ( ‘Atiyyah) said “I met Ibn ‘Umar in Al-Balaat so I mentioned Abu Sa’eed’s hadith from the Prophet (ﷺ). So he said and pointed to his ears ‘My two ears heard it, and my heart preserved it.’ “
Grade:

Hadith #3305 - Sunan Ibn Majah - Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Anas ibn Malik; Hisham bin Zayd bin Anas هشام بن زيد بن أنس بن مالك; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“O my nephew! I heard the Messenger of Allah (ﷺ) saying ‘Whoever let his garment drag out of pride, Allah will not look at him on the Day of Resurrection.’”
Grade:

Hadith #3306 - Sunan Ibn Majah - Abdur Rahman bin 'Abdul Malik bin Shayb عبد الرحمن بن عبد الملك بن شيبة; Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Abbas; Ikrama عكرمة; Smak bin Hrb bin Aws سماك بن حرب بن أوس; Sufyan bin 'Uyaynah سفيان بن عيينة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) took hold of the lower part of my calf or his calf and said: ‘This is where the lower wrap should come to. If you insist, then lower, and if you insist, then lower, but the lower wrap has no right to (come to) the ankle.’”
Grade:

Hadith #3307 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“I said to Abu Sa’eed: ‘Did you hear anything from the Messenger of Allah (ﷺ) concerning the lower wrap?’ He said: ‘Yes. I heard the Messenger of Allah (ﷺ) say: ‘The lower wrap of the believer should come to mid-calf, but there is no sin on him if it comes between that point and the ankle. But whatever is lower than the ankle is in the Fire.’ And he said three times: ‘Allah will not look at the one who lets his lower wrap drag out of vanity.’”
Grade:

Hadith #3308 - Sunan Ibn Majah - Abdullah bin Abi Najih عبد الله بن أبي نجيح; Ibn Ishaq محمد بن إسحاق بن يسار‎; ibn Umar; Mujahid bin Jabir مجاهد بن جبر; Swyd bin Sa'id سويد بن سعيد; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة (Sunan Ibn Majah)
“O Sufyan bin Sahl, do not let your garment hang, for Allah does not like those who let their garments hang below the ankles.’”
Grade:

Hadith #3309 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Asma' bint Abi Bakr; Fatima bint al-Mundhir bin al-Zubayr فاطمة بنت المنذر بن الزبير; Hisham bin 'Urwa هشام بن عروة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
There was no garment more beloved to the Messenger of Allah (ﷺ) than the shirt.”
Grade:

Hadith #3310 - Sunan Ibn Majah - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; Bakr bin Khlf al-Basri بكر بن خلف البصري; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Ibn Majah)
“Hanging down may apply to the waist wrap, shirt or turban. Whoever lets any of these drag out of pride, Allah will not look at him on the Day of Resurrection.”
Grade:

Hadith #3311 - Sunan Ibn Majah - Abdullah bin Abi Awfa; Ali bin Ms'hr علي بن مسهر; Sulaiman bin Abi Sulaiman سليمان بن أبي سليمان; Swyd bin Sa'id سويد بن سعيد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to wear a shirt that was short in the sleeves and length.”
Grade:

Hadith #3312 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Mu'awiya bin Salah bin Hadayr معاوية بن صالح بن حدير; Zayd bin al-Habab al-'Akli زيد بن الحباب أبو الحسين العكلي (Sunan Ibn Majah)
“I came to the Messenger of Allah (ﷺ) and gave him my pledge, and the buttons of his shirt were undone.”
Grade:

Hadith #3313 - Sunan Ibn Majah - al-Bara' bin Azib bin al-Harith; Ali bin Ms'hr علي بن مسهر; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Swyd bin Sa'id سويد بن سعيد (Sunan Ibn Majah)
“The Prophet (ﷺ) came to us and haggled with us over the price of trousers.”
Grade:

Hadith #3314 - Sunan Ibn Majah - al-Mughira bin 'Abdur Rahman - Qusayy المغيرة بن عبد الرحمن بن عبد الله - قصي; Salma ibn al-Akwa; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني; Yazid bin Abi 'Ubaid يزيد بن أبي عبيد (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) was asked about how long a woman’s hem should hang down. He said: ‘A hand span.’ I said: ‘But then (her legs and feet) will be uncovered.’ He said: ‘Then a forearm’s length, but no more than that.’”
Grade:

Hadith #3315 - Sunan Ibn Majah - Abdur-Razzaq عبد الرزاق بن همام; Anas ibn Malik; Ayoub al-Sakhtiyani أيوب السختياني; Ibn Sirin محمد بن سيرين الأنصاري; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Ibn Majah)
“The wives of the Prophet (ﷺ) were allowed to let their hems hang down, so they used to come to us and we would measure one forearms length for them with a reed.”
Grade:

Hadith #3316 - Sunan Ibn Majah - Abdul al-Kareem bin Malik عبد الكريم بن مالك الجزري أبو سعيد; Abdur-Razzaq عبد الرزاق بن همام; Ata' bin Abi Rabah عطاء بن أبي رباح; Jabir ibn 'Abdullah; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“Let your hem down one forearm’s length.”
Grade:

Hadith #3317 - Sunan Ibn Majah - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Khalid bin al-Walid; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“A hand span.” ‘Aishah said: “This may show her calves.” He said: “Then a forearm’s length.”
Grade:

Hadith #3318 - Sunan Ibn Majah - Abdullah bin Mubarak عبد الله بن المبارك; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; Jabir Bun Nauf, Abu al-Wadak جبر بن نوف أبو الوداك; Mujalid bin Sa'id bin 'Umayr مجالد بن سعيد الهمداني; Sulaiman bin Hayan al-Azdi سليمان بن حيان الأزدي (Sunan Ibn Majah)
“I saw the Prophet (ﷺ) delivering a sermon on the pulpit, wearing a black turban.”
Grade:

Hadith #3319 - Sunan Ibn Majah - Abdullah bin Mughfal al-Mazni; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Matruf bin Tarayf al-Harithi مطرف بن طريف; Shababa bin Sawar شبابة بن سوار الفزاري; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Yazid bin Hameed, Abu Tiyah يزيد بن حميد أبو التياح الضبعي (Sunan Ibn Majah)
It was narrated from Jabir that the Prophet (ﷺ) entered Makkah wearing a black turban.
Grade:

Hadith #3320 - Sunan Ibn Majah - Abdullah bin Mughfal al-Mazni; Matruf bin Tarayf al-Harithi مطرف بن طريف; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس; Yazid bin Hameed, Abu Tiyah يزيد بن حميد أبو التياح الضبعي (Sunan Ibn Majah)
It was narrated from Ibn ‘Umar that the Prophet (ﷺ) entered (Makkah), on the Day of the Conquest of Makkah, wearing a black turban.
Grade:

Hadith #3321 - Sunan Ibn Majah - ibn Umar; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Nafie' نافع مولى ابن عمر; Swyd bin Sa'id سويد بن سعيد (Sunan Ibn Majah)
“It is as if I can see the Messenger of Allah (ﷺ), wearing a black turban, with the ends hanging down his shoulders.”
Grade:

Hadith #3322 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Ibn Majah)
“Whoever wears silk in this world will not wear it in the Hereafter.”
Grade:

Hadith #3323 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade brocade, silk, and embroidered brocade.”
Grade:

Hadith #3324 - Sunan Ibn Majah - Abdullah bin Mughfal al-Mazni; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Hasan al-Basri الحسن البصري; Yonus bin 'Ubaid bin Dinar يونس بن عبيد بن دينار العبدي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade wearing silk and gold. He said: ‘They are for them in this world and for us in the Hereafter.’”
Grade:

Hadith #3325 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Sa'ib bin Yazid bin Akht Namr; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Khalid bin Mukhallad al-Qatwani خالد بن مخلد القطواني; Sufyan bin Abi Zuhyr; Yazid bin 'Abdullah bin Khusayfa يزيد بن عبد الله بن خصيفة (Sunan Ibn Majah)
“O Messenger of Allah, why don’t you buy this two piece suit (to wear for meeting) the delegations, and on Fridays?” The Messenger of Allah (ﷺ) said: “This is only worn by one who has no share in the Hereafter.”
Grade:

Hadith #3326 - Sunan Ibn Majah - Abu Idrees al-Khulani أبو إدريس الخولاني; Abu Tha'laba al-Khushni; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Rabi'a bin Yazid al-Damashqi ربيعة بن يزيد الدمشقي (Sunan Ibn Majah)
It was narrated from Anas bin Malik that the Messenger of Allah (ﷺ) granted a concession to Zubair bin ‘Awwam and ‘Abdur-Rahman bin ‘Auf, allowing them to wear silk shirts, because of a rash they were suffering from.
Grade:

Hadith #3327 - Sunan Ibn Majah - Adi ibn Hatim al-Tayyi'; Amir al-Sha'bi عامر الشعبي; Byan bin Bashr al-Ahmsi بيان بن بشر الأحمسي; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان (Sunan Ibn Majah)
Then he gestured with his finger, then a second, and a third, and a fourth (i.e., the width of four fingers), and he said: “The Messenger of Allah (ﷺ) used to forbid it.”
Grade:

Hadith #3328 - Sunan Ibn Majah - al-Qasim bin Abi Bzh القاسم بن أبي بزة; Hajjaj bin Artah حجاج بن أرطاة; Jabir ibn 'Abdullah; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“I saw Ibn ‘Umar buying a turban that had some markings, then he called for a pair of scissors and cut that off. I entered upon Asma’ and mentioned that to her, and she said: ‘May ‘Abdullah perish, O girl! Give me the garment of the Messenger of Allah (ﷺ).’ A garment was brought that was hemmed with brocade on the sleeves, necklines and openings (at the front and back).”
Grade:

Hadith #3329 - Sunan Ibn Majah - Abdullah bin al-Samit عبد الله بن الصامت; Abu Dharr al-Ghaffari; Hameed bin Hilal حميد بن هلال; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) took hold of some silk in his left hand and some gold in his right, then he raised his hands and said: ‘These two are forbidden for the males of my nation, and permitted to the females.’”
Grade:

Hadith #3330 - Sunan Ibn Majah - Abdur Rahman bin 'Amr al-Awza'i عبد الرحمن بن عمرو أبو عمرو الأوزاعي; Abu Tha'laba al-Khushni; Dmrh bin Rabi'ya al-Flstyny ضمرة بن ربيعة الفلسطيني أبو عبد الله; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yahya bin Sa'id al-Ansari يحيى بن سعيد الأنصاري (Sunan Ibn Majah)
“O Messenger of Allah, what should I do with these? Shall I wear them?” He said: “No, rather make them into head-cloths and give them to the Fatimahs.”**
Grade:

Hadith #3331 - Sunan Ibn Majah - Adi ibn Hatim al-Tayyi'; Amir al-Sha'bi عامر الشعبي; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Mujalid bin Sa'id bin 'Umayr مجالد بن سعيد الهمداني (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) came out to us, and in one of his hands was a garment of silk and in the other was some gold. He said: ‘These are forbidden to the males of my nation and permitted to the females.’”
Grade:

Hadith #3332 - Sunan Ibn Majah - Abdur-Razzaq عبد الرزاق بن همام; Adi ibn Hatim al-Tayyi'; Amir al-Sha'bi عامر الشعبي; Asim al-Ahwal عاصم الأحول; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Ibn Majah)
“I saw Zainab the daughter of the Messenger of Allah (ﷺ) wearing a shirt of Siyara’ silk.*
Grade:

Hadith #3333 - Sunan Ibn Majah - Adi ibn Hatim al-Tayyi'; Amir al-Sha'bi عامر الشعبي; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Waki' bin al-Jarrah وكيع بن الجراح; Zakaria bin Abi Za'idah زكريا بن أبي زائدة خالد (Sunan Ibn Majah)
“I never saw anyone more handsome then the Messenger of Allah (ﷺ), with his hair combed, wearing a red two-piece suit.”
Grade:

Hadith #3334 - Sunan Ibn Majah - Adi ibn Hatim al-Tayyi'; al-Jarrah bin Malih bin 'Ady الجراح بن مليح بن عدي; Hamam bin al-Harith همام بن الحارث; Ibrahim al-Nakha'i إبراهيم النخعي; Mansur bin al-Ma'tamar al-Salmi منصور بن المعتمر بن عبد الله السلمي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
I saw the Messenger of Allah (ﷺ) delivering a sermon, and Hasan and Husain came forward, wearing red shirts, stumbling and getting up again. The Prophet (ﷺ) stepped down, picked them up and put them in his lap. Then he said: “Allah and His Messenger have spoken the truth. ‘Your wealth and your children are only a trial.’ I saw these two and I could not be patient. Then he resumed his sermon.”
Grade:

Hadith #3335 - Sunan Ibn Majah - Hisham bin Sa'd al-Madni هشام بن سعد المدني أبو عباد; ibn Umar; Ma'n bin 'Isa bin Yahya معن بن عيسى بن يحيى; Y'aqub bin Hmyd bin Kasb يعقوب بن حميد بن كاسب المدني; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade Al-Mufaddam.”
Grade:

Hadith #3336 - Sunan Ibn Majah - Abu Bakr al-Hdhly أبو بكر الهذلي; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Isma'il bin Ayyash bin Saleem إسماعيل بن عياش بن سليم; Shar bin Hushab al-Asha'ri شهر بن حوشب الأشعري; Tamim al-Dari (Sunan Ibn Majah)
“I heard ‘Ali say: ‘The Messenger of Allah (ﷺ) forbade me – and I do not say that he forbade you – from wearing clothes dyed with safflower.’”
Grade:

Hadith #3337 - Sunan Ibn Majah - Abdur Rahman bin Zayd bin Aslam عبد الرحمن بن زيد بن أسلم العدوي; Ahmed bin Abi Bakr أبو مصعب أحمد بن أبي بكر; ibn Umar; Zayd bin Aslam زيد بن أسلم (Sunan Ibn Majah)
“We came with the Messenger of Allah (ﷺ) was Thaniyyat Adhakhir. He turned to me, and I was wearing a thin cloak dyed with safflower, and said: ‘What is this?’ And I realized that he disliked it. I came to my family when they were heating their oven and threw it (in the oven). Then I came to him the following day and he said: ‘O ‘Abdullah, what happened to the thin cloak?’ I told him (what I had done) and he said: ‘Why did you not give it to some of your family to wear, for there
Grade:

Hadith #3338 - Sunan Ibn Majah - Abu 'Uthman al-Nahdi عبد الرحمن بن مل - أبو عثمان النهدي; Salman Farsi (Sunan Ibn Majah)
“The Prophet (ﷺ) came to us and we gave him some water with which to cool down. He bathed, then I brought him a yellow blanket, and I saw the traces of Wars (the yellow dye) on the folds of his stomach.”
Grade:

Hadith #3339 - Sunan Ibn Majah - Ahmed bin Manay' أحمد بن منيع; Anas ibn Malik; Sa'id bin al-Mrzban al-Bsy سعيد بن المرزبان العبسي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Eat and drink, give charity and wear clothes, as long as that does not involve any extravagance or vanity.’”
Grade:

Hadith #3340 - Sunan Ibn Majah - Anas ibn Malik; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Jabir ibn 'Abdullah (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Whoever wears a garment of pride and vanity, Allah will clothe him, on the Day of Resurrection, in a garment of humiliation.’”
Grade:

Hadith #3341 - Sunan Ibn Majah - Abu Hurairah; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Hammad bin Salama حماد بن سلمة; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘Whoever wears a garment of pride and vanity in this world, Allah will clothe him in a garment of humiliation on the Day of Resurrection, then set it ablaze.’”
Grade:

Hadith #3342 - Sunan Ibn Majah - Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Abu Hurairah; Ibrahim bin al-Fadl al-Makhzumi إبراهيم بن الفضل المخزومي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Sa'id bin Abi Sa'id (Sunan Ibn Majah)
“Whoever wears a garment of pride and vanity, Allah will turn away from him until he takes it off.”
Grade:

Hadith #3343 - Sunan Ibn Majah - Abdur-Razzaq عبد الرزاق بن همام; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Ubaydullah bin 'Abdullah bin 'Utba عبيد الله بن عبد الله بن عتبة بن مسعود (Sunan Ibn Majah)
“I heard the Messenger of Allah (ﷺ) say: ‘Any skin that has been tanned has been purified.’”
Grade:

Hadith #3344 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Ahmed bin 'Isa bin Hassan - al-Tastari أحمد بن عيسى بن حسان - التستري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Ibn Majah)
“Why don’t they take its skin and ten it, and make us of it?” They said: “O Messenger of Allah, it is dead meat.”* He said: “It is only unlawful to eat it.”
Grade:

Hadith #3345 - Sunan Ibn Majah - Abu Salah Maula 'Uthman أبو صالح مولى عثمان; al-Laith bin Sa'd الليث بن سعد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Ibn Majah)
“One of the Mothers of the Believers had a sheep that died. The Messenger of Allah (ﷺ) passed by it and said: ‘It would not have harmed its owners if they had made use of its hide.’”
Grade:

Hadith #3346 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Ayoub al-Sakhtiyani أيوب السختياني; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) commanded that use should be made of the skins of dead animals, if they were tanned.”
Grade:

Hadith #3347 - Sunan Ibn Majah - Abdullah bin Mughfal al-Mazni; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج; Ubaid bin Sa'id bin Aban bin Sa'id عبيد بن سعيد بن أبان بن سعيد; Uqba bin S'hban عقبة بن صهبان (Sunan Ibn Majah)
“There came to us a letter from the Prophet (ﷺ) (saying): ‘No not make use of the untanned skin and sinew of dead animals.’”
Grade:

Hadith #3348 - Sunan Ibn Majah - Abdul Hameed bin Jubayr bin Shayba عبد الحميد بن جبير بن شيبة بن عثمان; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Sa'id ibn al-Musayyib سعيد بن المسيب بن حزن أبو محمد القرشي; Sufyan bin 'Uyaynah سفيان بن عيينة; Umm Shareek (Sunan Ibn Majah)
“The sandals of the Prophet (ﷺ) had two thongs doubled around their straps.”
Grade:

Hadith #3349 - Sunan Ibn Majah - Abdul 'Aziz bin al-Mukhtar عبد العزيز بن المختار; Abu Hurairah; Ibn Abi al-Shuwarab محمد بن عبد الملك بن أبي الشوارب (Sunan Ibn Majah)
“The sandals of the Prophet (ﷺ) had two thongs.”
Grade:

Hadith #3350 - Sunan Ibn Majah - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Urwa ibn al-Zubayr عروة بن الزبير; Yonus bin Yazid bin Abi al-Nijad يونس بن يزيد بن أبي النجاد (Sunan Ibn Majah)
“When anyone of you puts on his sandals, let him start with the right, and when he takes them off, let him start with the left.”
Grade:

Hadith #3351 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Nafie' نافع مولى ابن عمر; Yonus bin Muhammad bin Muslim يونس بن محمد بن مسلم المؤدب (Sunan Ibn Majah)
It was narrated from Abu Hurairah that the Messenger of Allah (ﷺ) said; “None of you should walk in one sandal or in one leather sock. Let him take them both off or walk in both of them.”
Grade:

Hadith #3352 - Sunan Ibn Majah - Abu Idrees al-Khulani أبو إدريس الخولاني; Abu Tha'laba al-Khushni; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade putting on sandals whilst standing.”
Grade:

Hadith #3353 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Ahmed bin Snan bin Asad أحمد بن سنان بن أسد; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Ishaq bin Mansur al-Kausaj إسحاق بن منصور بن بهرام - الكوسج; Isma'il bin Abi Hkym إسماعيل بن أبي حكيم القرشي; Mua'wiya bin Hisham al-Qsar معاوية بن هشام القصار (Sunan Ibn Majah)
“The Prophet (ﷺ) forbade putting on sandals whilst standing.”
Grade:

Hadith #3354 - Sunan Ibn Majah - Bakr bin Khlf al-Basri بكر بن خلف البصري; ibn Abbas; Maymun bin Mahran ميمون بن مهران; Muhammad bin Abi 'Adi محمد بن أبي عدي; Sa'id bin Abi Sa'id; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Ibn Majah)
It was narrated from Ibn Buraidah, from his father, that an-Najashi sent a pair of pure black Khuff as a gift to the Prophet (ﷺ) of, which he wore.
Grade:

Hadith #3355 - Sunan Ibn Majah - Abdul Karim bin Abi al-Mukharaq عبد الكريم بن أبي المخارق; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hibban bin Jaz'; Ibn Ishaq محمد بن إسحاق بن يسار‎ (Sunan Ibn Majah)
“The Jews and the Christians do not dye (their hair), so differ from them.”
Grade:

Hadith #3356 - Sunan Ibn Majah - Abdullah bin 'Ubaid bin 'Umayr عبد الله بن عبيد بن عمير; Abdullah bin Raja' al-Makki عبد الله بن رجاء المكي أبو عمران; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو; Jabir ibn 'Abdullah; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي (Sunan Ibn Majah)
“The best things with which you change gray hair are henna and Katam.”*
Grade:

Hadith #3357 - Sunan Ibn Majah - Abdul Karim bin Abi al-Mukharaq عبد الكريم بن أبي المخارق; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hibban bin Jaz'; Ibn Ishaq محمد بن إسحاق بن يسار‎ (Sunan Ibn Majah)
“I entered upon Umm Salamah and she brought out for me a hair of the Messenger of Allah (ﷺ), which was dyed with henna and Katam.”
Grade:

Hadith #3358 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Husayn bin 'Abdur Rahman al-Salmi حصين بن عبد الرحمن السلمي; Muhammad bin Fadayl bin Ghazwan محمد بن فضيل بن غزوان; Thabit bin Yazid al-Ahwl ثابت بن يزيد الأحول; Zayd bin Wahb al-Jhny زيد بن وهب الجهني (Sunan Ibn Majah)
“Abu Quhaifah was brought to the Prophet (ﷺ) on the Day of the Conquest (of Makkah), and his head was all white. The Messenger of Allah (ﷺ) said: ‘Take him to some of his womenfolk and let them change this, but avoid black.’”
Grade:

Hadith #3359 - Sunan Ibn Majah - Jabir ibn 'Abdullah; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) said: ‘The best thing with which you can dye your hair is this black (dye). It makes your women desire you and creates fear in the hearts of your enemies.’”
Grade:

Hadith #3360 - Sunan Ibn Majah - Abdul A'ala bin 'Abdul A'ala al-Sami عبد الأعلى بن عبد الأعلى البصري السامي; Jabir ibn 'Abdullah; Qatada قتادة; Sa'id bin Abi 'Aruba سعيد بن أبي عروبة; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث; Umar ibn al-Khattab (Sunan Ibn Majah)
“I see that you dye your beard yellow with Wars.” Ibn ‘Umar said: “As for my dyeing of my beard yellow with Wars, I saw the Messenger of Allah (ﷺ) dyeing his beard yellow.”
Grade:

Hadith #3361 - Sunan Ibn Majah - Abdul Rahim bin Sulaiman عبد الرحيم بن سليمان الكناني; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Sa'id al-Khudri; al-Mandhar bin Malik bin Qata' المنذر بن مالك بن قطعة - أبو نضرة العبدي; Da'ud bin Abi Hnd داود بن أبي هند (Sunan Ibn Majah)
“The Prophet (ﷺ) passed by a man who had dyed his hair with henna and said: ‘How handsome this is!’ Then he passed by another who had dyed his hair with henna and Katam, and said: ‘This one is more handsome than that one.’ Then he passed by another who had dyed his hair yellow and said: ‘This one is more handsome than all of them.’”
Grade:

Hadith #3362 - Sunan Ibn Majah - Abu Umama bin Sahl; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Abbas; Khalid bin al-Walid; Muhammad bin al-Walid al-Zubaidi محمد بن الوليد بن عامر الزبيدي; Muhammad bin Harb al-Wasti محمد بن حرب بن حرمان النشائي (Sunan Ibn Majah)
“I saw the Messenger of Allah (ﷺ), and this part of his hair was white” – meaning the tuft of hair between the lower lip and the chin.
Grade:

Hadith #3363 - Sunan Ibn Majah - Abdullah bin Dinar عبد الله بن دينار العدوي; ibn Umar; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“Anas bin Malik was asked: ‘Did the Messenger of Allah (ﷺ) dye his hair?’ He said: ‘He did not have any white hair apart from approximately seventeen or twenty hairs at the front of his beard.’”
Grade:

Hadith #3364 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Anas ibn Malik; Hisham bin Zayd bin Anas هشام بن زيد بن أنس بن مالك; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“The white hair of the Prophet (ﷺ) numbered approximately twenty.”
Grade:

Hadith #3365 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amir al-Sha'bi عامر الشعبي; Da'ud bin Abi Hnd داود بن أبي هند; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
“Umm Hani said: ‘When the Messenger of Allah (ﷺ) entered Makkah he had four braids.’”
Grade:

Hadith #3366 - Sunan Ibn Majah - Abdul Karim bin Abi al-Mukharaq عبد الكريم بن أبي المخارق; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Hibban bin Jaz'; Ibn Ishaq محمد بن إسحاق بن يسار‎ (Sunan Ibn Majah)
“The People of the Book used to let their hair hang down, and the idolaters used to part their hair. The Messenger of Allah (ﷺ) liked to be more like the People of the Book. So the Messenger of Allah (ﷺ) let his forelock hang down, then after that he parted it.”
Grade:

Hadith #3367 - Sunan Ibn Majah - Abu Hurairah; al-Mughira bin Abi Burda المغيرة بن أبي بردة; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Imam Maalik مالك بن أنس بن مالك بن أبي عامر; Sa'id bin Salmah bin Aby سعيد بن سلمة بن أبي; Safwan bin Slym al-Madni صفوان بن سليم المدني أبو عبد الله (Sunan Ibn Majah)
“I used to part the hair of the Messenger of Allah (ﷺ) behind his crown, and let his forelock hang down.”
Grade:

Hadith #3368 - Sunan Ibn Majah - Ahmed bin 'Ubda bin Musa أحمد بن عبدة بن موسى; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Ibn Majah)
“The hair of the Messenger of Allah (ﷺ) was wavy, and (hung down) between his ears and his shoulders.”
Grade:

Hadith #3369 - Sunan Ibn Majah - Ahmed bin al-Azhar bin Mny' أحمد بن الأزهر بن منيع; al-Hythm bin Jmyl الهيثم بن جميل; Hisham bin 'Urwa هشام بن عروة; ibn Umar; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) had hair that came between his earlobes and his shoulders.”
Grade:

Hadith #3370 - Sunan Ibn Majah - Abdur Rahman bin 'Abdullah bin 'Utba عبد الرحمن بن عبد الله بن عتبة المسعودي; Aisha bint Abi Bakr; Muhammad bin 'Abdullah al-Ansari محمد بن عبد الله بن المثني - الأنصاري; Muhammad bin Bashar Bindar محمد بن بشار بندار (Sunan Ibn Majah)
“The Prophet (ﷺ) saw me when I had long hair. He said: ‘Bad news, bad news!’ So I went away and cut it short. Then the Prophet (ﷺ) saw me and said: ‘I did not mean you, but this is better.’”
Grade:

Hadith #3371 - Sunan Ibn Majah - Abdur-Razzaq عبد الرزاق بن همام; al-Husain bin Mhdy bin Malik الحسين بن مهدي بن مالك; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade Qaza’.” He (Nafi’) said: “What is Qaza’?” He said: “It means shaving part of a child’s head and leaving another part.”
Grade:

Hadith #3372 - Sunan Ibn Majah - Abdullah bin Saalam; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Hammad bin Usamah حماد بن أسامة - أبو أسامة; Zararah bin Awfa al-'Amiri al-Harshi زرارة بن أوفى العامري الحرشي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade Qaza’.”
Grade:

Hadith #3373 - Sunan Ibn Majah - Hajjaj bin Muhammad al-Musaysi حجاج بن محمد المصيصي الأعور; Ibn Jurayj ابن جريج; ibn Umar; Muhammad bin Yahya bin 'Abdul Karim محمد بن يحيى بن عبد الكريم; Nafie' نافع مولى ابن عمر; Sulaiman bin Musa al-Ashdaq سليمان بن موسى الأموي الأشدق (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) wore a ring of silver, then he had engraved on it (the words) ‘Muhammad Rasul Allah’ (Muhammad the Messenger of Allah). And he said: ‘No one should have his ring engraved like this ring of mine.’”
Grade:

Hadith #3374 - Sunan Ibn Majah - al-Laith bin Sa'd الليث بن سعد; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) had a ring made for him, and he said: ‘I have had a ring made for me and had it engraved, and no one should make a ring with similar engraving.’”
Grade:

Hadith #3375 - Sunan Ibn Majah - Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Yahya bin Ziyad bin Abi Da'ud, Fahayr يحيى بن زياد بن أبي داود الأسدي فهير (Sunan Ibn Majah)
‘Muhammad Rasul Allah’ (Muhammad the Messenger of Allah).”
Grade:

Hadith #3376 - Sunan Ibn Majah - al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; al-Hasan bin Musa al-'Ashayb الحسن بن موسى الأشيب; Amr bin Dinar al-Basri عمرو بن دينار البصري الأعور قهرمان; ibn Umar; Sa'id bin Zayd; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Umar ibn al-Khattab (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade wearing gold rings.”
Grade:

Hadith #3377 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Ady bin Thabit al-Ansari عدي بن ثابت الأنصاري الكوفي; Affan bin Muslim عفان بن مسلم بن عبد الله الصفار; Muhammad bin Bashar Bindar محمد بن بشار بندار; Muhammad bin Ja'far bin Abi Kathir محمد بن جعفر بن أبي كثير; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade gold rings.”
Grade:

Hadith #3378 - Sunan Ibn Majah - Abdullah bin Numayr عبد الله بن نمير; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; ibn Umar; Nafie' نافع مولى ابن عمر; Ubaidullah bin 'Umar bin Hafs عبيد الله بن عمر بن حفص بن عاصم (Sunan Ibn Majah)
“Najashi sent some jewelry as a gift to the Messenger of Allah (ﷺ). Among that was a gold ring with an Ethiopian gemstone. The Messenger of Allah (ﷺ) picked it up with a stick – as if he found it distasteful – or with one of his fingers, then he called for his daughter, Umamah bint Abul-‘As, and said: ‘Wear this, O my daughter.’”
Grade:

Hadith #3379 - Sunan Ibn Majah - Abu Barda bin Abi Musa al-Asha'ari أبو بردة / الحارث بن أبي موسى الأشعري; Abu Karayb, Muhammad bin al-'Ala' محمد بن العلاء - أبو كريب; Abu Musa al-Asha'ari; Bryd bin 'Abdullah بريد بن عبد الله بن أبي; Hammad bin Usamah حماد بن أسامة - أبو أسامة (Sunan Ibn Majah)
It was narrated from Ibn ‘Umar that the Prophet (ﷺ) used to wear (his ring) with the stone nearest his palm.
Grade:

Hadith #3380 - Sunan Ibn Majah - Abdur Rahman bin Mahdi عبد الرحمن بن مهدي; Abu Hurairah; Muhammad bin Bashar Bindar محمد بن بشار بندار; Salman Abu Hazam al-Ashja'i سلمان أبو حازم الأشجعي; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
It was narrated from Anas bin Malik that the Messenger of Allah (ﷺ) wore a silver ring with an Ethiopian gemstone, and he used to ear the stone in towards his palm.
Grade:

Hadith #3381 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Abu Hurairah; Muhammad bin Khazim al-Darir محمد بن خازم أبو معاوية الضرير; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Ibn Majah)
It was narrated from ‘Abdullah bin Ja’far that the Prophet (ﷺ) used to wear a ring on his right hand.
Grade:

Hadith #3382 - Sunan Ibn Majah - Anas ibn Malik; Jabbarh bin al-Mghls al-Hmany Abu جبارة بن المغلس; Kathir bin Slym al-Dby كثير بن سليم الضبي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade me to wear a ring on this and on this,” meaning the little finger and the thumb.
Grade:

Hadith #3383 - Sunan Ibn Majah - Abu Hurairah; Amr bin Dinar عمرو بن دينار الأثرم الجمحي; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Ja'far bin Msafr bin Rashid جعفر بن مسافر بن راشد; Muhammad bin Jahada محمد بن جحادة; Zuhayr bin Mua'wiya bin Hudayj زهير بن معاوية بن حديج (Sunan Ibn Majah)
“The angels do not enter a house in which there is a dog or an image.”
Grade:

Hadith #3384 - Sunan Ibn Majah - Abu Juhayfa al-Sawai'; Ali bin al-Aqmar bin 'Amr علي بن الأقمر بن عمرو; Mas'ar bin Kadam مسعر بن كدام; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة (Sunan Ibn Majah)
“The angels do not enter a house in which there is a dog or an image.”
Grade:

Hadith #3385 - Sunan Ibn Majah - Abdullah bin Basr al-Maazni; Amr bin 'Uthman عمرو بن عثمان بن عفان; Muhammad bin 'Abdur Rahman bin 'Arq محمد بن عبد الرحمن بن عرق; Uthman ibn 'Affaan (Sunan Ibn Majah)
“Jibril (as) promised the Messenger of Allah (ﷺ) that he would come to him at a certain hour, but he was late. The Prophet (ﷺ) went out and there was Jibril standing at the door. He said: ‘What kept you from entering?’ He said: ‘There is a dog in the house, and we do not enter a house in which there is a dog or an image.’”
Grade:

Hadith #3386 - Sunan Ibn Majah - Abdullah bin 'Ubaid bin 'Umayr عبد الله بن عبيد بن عمير; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Aisha bint Abi Bakr; Badayl bin Maysarah بديل بن ميسرة; Hisham bin Abi 'Abdullah al-Dastawa'i هشام بن أبي عبد الله الدستوائي; Yazid bin Harun يزيد بن هارون (Sunan Ibn Majah)
It was narrated from Abu Umamah that a woman came to the Prophet (ﷺ) and told him that her husband was away on some military campaign. She asked him for permission to make an image of a palm tree in her house, and he did not let her, or he forbade her.
Grade:

Hadith #3387 - Sunan Ibn Majah - Hisham bin 'Urwa هشام بن عروة; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Umar bin Abi Salamah; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Ibn Majah)
“I covered a small room closet of mine, meaning, from the inside, with a curtain on which there were images. When the Prophet (ﷺ) came, he tore it down, so I made two pillows from it, and I saw the Prophet (ﷺ) reclining on one of them.”
Grade:

Hadith #3388 - Sunan Ibn Majah - Abu Hurairah; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Haql bin Ziyad; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Hisham bin Hassan al-Azdi هشام بن حسان الأزدي القردوسي; Yahya bin Abi Kathir يحيى بن أبي كثير الطائي (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) forbade rings of gold and Al-Mitharah,”* meaning the red ones.
Grade:

Hadith #3389 - Sunan Ibn Majah - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; al-Walid bin Kathir al-Makhzumi الوليد بن كثير المخزومي; Muhammad bin al-Sabah محمد بن الصباح البزاز الدولابي; Sufyan bin 'Uyaynah سفيان بن عيينة; Wahb bin Kysan al-Quraishi وهب بن كيسان القرشي (Sunan Ibn Majah)
“I heard Abu Raihanah, the Companion of the Prophet (ﷺ) say: ‘The Prophet (ﷺ) used to forbid riding on leopard skins.’”
Grade:

Hadith #3390 - Sunan Ibn Majah - al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muhammad bin Rmh bin al-Mhajr محمد بن رمح بن المهاجر (Sunan Ibn Majah)
“The Messenger of Allah (ﷺ) used to forbid riding on leopard skins.”
Grade: